A Two-Dimensional Assessment of China’s Approach Concerning the Compensation Fund for Ship-Induced Oil Pollution Damage: Pollution Governance and Victim Compensation - Cao, Xingguo; Chang, Yen-Chiang (Frontiers in Marine Science, 2022)
China has adopted a domestic approach to the compensation fund for ship-induced oil pollution damage by establishing the Chinese Ship-induced Oil Pollution Compensation (CSOPC) Fund. After almost 10 years of practice, there are still opinions and questions regarding the rationality of China’s domestic approach. This study reassesses China’s domestic approach by a two-dimensional analysis of the current position and potential developments of the CSOPC Fund’s functions in pollution governance and victim compensation. At the present stage, the goal of adequate compensation to victims is not well achieved by the CSOPC Fund when compared to its other goal of ensuring a better oil pollution emergency reaction. Given that the International Oil Pollution Compensation (IOPC) Fund is unlikely to contribute much to pollution governance, and the current inadequacy and defects of the CSOPC Fund can be improved gradually, it is suggested that China should continue its domestic approach with necessary improvements. Using the CSOPC Fund’s practice as a case study, this research intends to explore the pollution governance side of the compensation fund that has not yet been fully addressed, demonstrating the key value of the domestic fund compared to the IOPC Fund.